Penerapan Viewboard Informatif Pada Asosiasi Perguruan Tinggi Swasta Indonesia Dalam Era Industri 4.0 - Rahardja, Untung; Lutfiani, Ninda; Yolandari, Aulia (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2019)
Current technological developments are faced with the challenge of meeting the increasing world demand for capital goods and consumer goods simultaneously ensuring the continued evolution of human existence in its social, environmental and economic dimensions. The creation of industrial value at the beginning of industrial countries was formed by developments towards the fourth stage of industrialization, called Industry 4.0. At present, the dissemination of information about education and communication media such as the APTISI Website is carried out up to date and summarized in the viewboard. problem solving in this system is a viewboard-based information system on an official site that is used as a place or container and the dissemination of information specifically for its members and can display activities owned by organizations and institutions. To overcome this challenge the education method must also be followed by technological developments. In this study using two methods, namely the Use Case method and SWOT Analysis. With this research, it is expected to be able to gather association activities and can provide better results in the delivery of article information in the official site. Keywords: Industry 4.0, Viewboard, Official Site.